TOKOH PEREMPUAN DALAM NOVEL MENEBUS IMPIAN KARYA ABIDAH EL KHALIEQY: KAJIAN FEMINISME - Janar Setiyanto; Rusdian Noor Dermawan (CARAKA, 2015)
The purpose of this study is as follows. (1) Describe the character and background of the novel redeem dream. (2) Describe the position of women in Islamic feminism in the novel makes up the dream. (3) Describe the struggle of women according to Islamic feminism in the novel make up the dream. The research is qualitative studies. Based on the research of the information from the text consisting of novel penetrating dreama paragraph or an event in novel penetrating dreama. The data source of this research is a novel Penetrate Dream. The instrument in this study is the researchers themselves who in Arm-specific set of science concepts related to the problems examined. Data collection techniques using the technique of reading the log. Data obtained through reading, concluded all data required for research purposes. The results obtained in this study, (1) the main character and background of the novel is the dream penetrating Nur figure adds Kumalajati young, beautiful, unyielding, independent, kind, friendly, thoughtful, sympathetic, strong in character, and student intelligent, while background is in a village where Sitibinangun, but moved to the city in Gang Mawar. (2) the position of female characters in the novel by the Islamic feminism redeem the dream, the position of women is closely related to the origin of the creation, recognition of Almighty God for the glory of women. Owned the rights and dignity of women equal to men. Nur Kumalajati so that to achieve success and pursue his dream he must work and strive aqual men, but did not leave their nature as female. (3) the struggle of famele characters in the novel by the Islamic feminism redeem the dream. Nur Kumalajati struggles to realize his dream finally realized that one hectare donating land to the boarding school, as well as other social activities.